Penilaian Kapasitas Fiskal Regional Melalui Partisipasi Langsung Modal Provinsi - Gusti Ngurah Rai; Aln Pujo Priambodo (Research and Development Agency Ministry of Home Affairs, 2026)
In order to accelerate socio-economic growth, local governments often allocate their budgets to direct expenditures and capital investments. However, an issue arose under strict budget constraints, exacerbated by unequal regional fiscal capacities to fund strategic development programs. Moreover, such instrument impacts have been variously debated across the study. This study was designed to examine the impact of provincial government direct capital participation (PMD) and various parameters on local fiscal capacity (IKFD) using path analysis, unveiling both direct and indirect effects. The data were collected from 34 provinces over the period 2017–2024. Mediatory variables, such as Local Fiscal Autonomy (LFA) and KDD, were also incorporated within the model. The findings highlighted the significant effects of PMD, gross fixed capital formation, LFA, and regional capital expenditure in corroborating local fiscal capacity, thereby increasing the urgency of management of the respective instruments. Ultimately, local fiscal capacity advancement through good governance will potentially return substantial benefits, providing more financial capacity for strengthening the socio-economic state and supporting national agendas.